Hubungan Amalan Pengurusan Kualiti Terlazim Dengan Prestasi Kerja Di Sektor Awam - Mohd. Fazil, Mahmood (2001)

(untitled)
Work performance is widely been used as one of the variables to measure an individual's work performance in an organisation. However, work performance also has a relationship with the organisational environment. One of them is through the best practice management adopted by many organisations including the public organisation. There are seven dimensions of the best practise management; top management influence, development of human resource management, system and process management, quality supplier management, customer value management, benchmarking and quality training. This study attempts to distinguish the relationship of the best practise management and employee's work performance in the public organisation. Also this study identifies the significant dimension that highly correlates with the employee's work performance in the public organisation. The sample comprises of 152 respondents in the State Secretary Department, Kedah. From the correlation analysis, this study concludes that all dimensions have significantly related to the employee's work performance. Based on regression analysis, the coefficient of determination, R2, equals 0.620, signifying that 62.0% of variation in the work performance was statistically explained or accounted for by the seven's dimension of best practice management. Customer value management, system and process management and quality training seems to be the significant dimension to distinguish the relationship of the best practice management and employee's work performance in the public organisation.